Phorbol esters inhibit the Hedgehog signalling pathway downstream of Suppressor of Fused, but upstream of Gli - Lauth, M; Bergström, Å; Toftgård, R (Oncogene, 2007)
The developmentally important Hedgehog (Hh) signal transduction pathway, which has recently been implicated in several forms of cancer, is subject to regulation by several protein kinases. Here, we address the role of protein kinase C δ in pathway inhibition and show that cellular depletion or pharmacological inhibition of this kinase isoform results in a blockade of signalling between Suppressor of Fused and the Gli transcription factors. We further provide evidence that the observed pathway inhibition is independent of primary cilia and the mitogen-activated protein kinase kinase (Mek1) kinase. These findings allowed for the rapid dissection of downstream Hh pathway activation mechanisms in human tumour cells and demonstrate a surprising variation in how cells can activate signalling in a ligand- and receptor-independent manner.